BRD4 is an atypical kinase that phosphorylates Serine2 of the RNA Polymerase II carboxy-terminal domain - Devaiah, Ballachanda N. (National Academy of Sciences, 2012)
The bromodomain protein, BRD4, has been identified recently as a therapeutic target in acute myeloid leukemia, multiple myeloma, Burkitt’s lymphoma, NUT midline carcinoma, colon cancer, and inflammatory disease; its loss is a prognostic signature for metastatic breast cancer. BRD4 also contributes to regulation of both cell cycle and transcription of oncogenes, HIV, and human papilloma virus (HPV). Despite its role in a broad range of biological processes, the precise molecular mechanism of BRD4 function remains unknown. We report that BRD4 is an atypical kinase that binds to the carboxyl-terminal domain (CTD) of RNA polymerase II and directly phosphorylates its serine 2 (Ser2) sites both in vitro and in vivo under conditions where other CTD kinases are inactive. Phosphorylation of the CTD Ser2 is inhibited in vivo by a BRD4 inhibitor that blocks its binding to chromatin. Our finding that BRD4 is an RNA polymerase II CTD Ser2 kinase implicates it as a regulator of eukaryotic transcription.